SOMATIZMLIK FRAZEOLOGIZMLERDIŃ LINGVOMÁDENIY IZERTLENIWI - Shınnazarova, S. (ILIM hám JÁMIYET, 2022)
The article deals with the questions of studying somatic phraseological units in the Turkic languages, including the Karakalpak language. Attention is paid to the analysis of somatic phraseological units in textbooks for higher educational institutions. An overview was given to the very first phraseological dictionaries published in the Karakalpak language. Critical remarks were considered about somatic phraseological units in the Karakalpak language, in particular in folklore works and the language of works of fiction.